Genetic analysis of adult leukoencephalopathy patients using a custom‐designed gene panel. Issue 2 (8th June 2018) - Kunii, M.; Doi, H.; Ishii, Y.; Ohba, C.; Tanaka, K.; Tada, M.; Fukai, R.; Hashiguchi, S.; Kishida, H.; Ueda, N.; Kudo, Y.; Kugimoto, C.; et al.
Abstract : Leukoencephalopathies encompass all clinical syndromes that predominantly affect brain white matter. Genetic diagnosis informs clinical management of these patients, but a large part of the genetic contribution to adult leukoencephalopathy remains unresolved. To examine this genetic contribution, we analyzed genomic DNA from 60 Japanese patients with adult leukoencephalopathy of unknown cause by next generation sequencing using a custom‐designed gene panel. We selected 55 leukoencephalopathy‐related genes for the gene panel. We identified pathogenic mutations in 8 of the 60 adult leukoencephalopathy patients (13.3%): NOTCH3 mutations were detected in 5 patients, and EIF2B2, CSF1R, and POLR3A mutations were found independently in 1 patient each. These results indicate that cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) caused by NOTCH3 mutations is the most frequent adult leukoencephalopathy in our cohort. Moreover, brain imaging analysis indicates that CADASIL patients who do not present typical phenotypes may be underdiagnosed if not examined genetically. Abstract : About 13.3% of adult patients with leukoencephalopathy were definitively disgnosed with known, apparently pathological or novel mutations.